POLA AKTIVITAS RUANG TERBUKA PUBLIK PADA KAWASAN TAMAN FATAHILLAH JAKARTA - Hantono, Dedi (Jurnal Arsitektur Komposisi, 2017)
Abstract: Fatahillah Park in front of Fatahillah Museum is part of Jakarta Kota area (called Kota Tua, Old Town) which is a conservation area. Fatahillah Park currently serves as a public open space surrounded by historic buildings on four sides. As a public open space, Taman Fatahillah is visited by people from various regions in Indonesia and foreign tourists, so there are various activities in it. This paper describes the results of research on the pattern of human activity (visitors) in Taman Fatahillah. The research used qualitative approach and descriptive analysis method. As a result, as a public open space, Taman Fatahillah is accessed by anyone and within the timeframe from morning to evening. Activities that take place in Taman Fatahillah are dominated by secondary actors (visitors) while the primary actors (traders) are limited by a certain place and time. The activity on the path space forms a linear pattern and on an open field forming a random pattern.Keywords:Â public open space, activities, area, conservation, urban designAbstrak: Taman Fatahillah di depan Museum Fatahillah adalah bagian dari kawasan Jakarta Kota (disebut Kota Tua) yang merupakan kawasan konservasi. Taman Fatahillah saat ini berfungsi sebagai ruang terbuka publik yang dikelilingi oleh bangunan-bangunan bersejarah pada empat sisi. Sebagai ruang terbuka publik, Taman Fatahillah didatangi orang-orang dari berbagai daerah di Indonesia dan wisatawan manca negara, sehingga muncul beragam aktifitas di dalamnya. Tulisan ini memaparkan hasil penelitian tentang pola aktivitas manusia (pengunjung) di Taman Fatahillah. Penelitian menggunakan pendekatan kualitatif dan metode analisis deskriptif. Hasilnya, sebagai ruang terbuka publik, Taman Fatahillah diakses oleh siapa saja dan dalam rentang waktu dari pagi hari hingga malam hari. Aktivitas yang berlangsung di Taman Fatahillah didominasi oleh pelaku sekunder (pengunjung) sedangkan pelaku primer (pedagang) dibatasi oleh tempat dan waktu tertentu. Aktivitas pada ruang jalan membentuk pola linier dan pada lapangan terbuka membentuk pola acak.Kata Kunci: ruang terbuka publik, aktivitas, kawasan, konservasi, rancang kota